2018
DOI: 10.2116/analsci.17p347
|View full text |Cite
|
Sign up to set email alerts
|

Fast Detection of Bismerthiazol in Cabbage Based on Fluorescence Quenching of Protein-Capping Gold Nanoclusters

Abstract: In this work, bismerthiazol was firstly assayed by a fast and portable method employing protein-capping gold nanoculsters as probes. The luminescent intensity of the nanoclusters showed a correlative response towards bismerthiazol from 5 to 4000 μg/mL with a linear relation in the range of 5 - 100 μg/mL. As little as 5 μg/mL of bismerthiazol could be quantified. The high affinity of bismerthiazol to interact with the soybean protein-capped gold nanoclusters contributed to the excellent selectivity of this meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A new method for detecting bismerthiazol [131], a commonly used fungicide in cabbage was developed using protein-capping gold nanoclusters (PC-GNCs). The PC-GNCs were synthesised using a simple, green method, and were then functionalised with the protein from soybeans to enhance their stability and biocompatibility.…”
Section: Biosensors With Bio-coatings and Applications In The Food Se...mentioning
confidence: 99%
“…A new method for detecting bismerthiazol [131], a commonly used fungicide in cabbage was developed using protein-capping gold nanoclusters (PC-GNCs). The PC-GNCs were synthesised using a simple, green method, and were then functionalised with the protein from soybeans to enhance their stability and biocompatibility.…”
Section: Biosensors With Bio-coatings and Applications In The Food Se...mentioning
confidence: 99%
“…For instance, bismerthiazol (BT), a commercial bactericide active against Xanthomonas oryzae pv. oryzae ( Xoo ), exhibits subchronic and chronic toxicity in humans upon oral consumption [ 9 ]. These drawbacks have highlighted the urgent need for safer and more environmentally responsible pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Up to now, Au NCs-based uorescence sensors are mainly dependent on the uorescence-quenching effect via the interactions between Au atoms and the analytes (such as bismerthiazol and Hg 2+ ). 13,14 Previous studies have shown that the uorescence behavior of Au NCs is not only highly size-dependent, but also correlated with the surface ligands and ligand density. 15 For example, Zhang et al 16 successfully prepared Au NC-based uorescent probes to detect glutathione (GSH) by signicantly enhancing the uorescence intensity of Au NCs, which inspired us to consider the possibility of broadening the applications by developing Au NCs with more functional ligands.…”
Section: Introductionmentioning
confidence: 99%